Eye‐tracking–based assessment suggests preserved well‐being in locked‐in patients. Issue 2 (23rd February 2017) - Linse, Katharina; Rüger, Wolfgang; Joos, Markus; Schmitz‐Peiffer, Henning; Storch, Alexander; Hermann, Andreas
Abstract : We assessed quality of life (QoL) and psychological well‐being in patients with amyotrophic lateral sclerosis–induced locked‐in state and their next of kin in a fully unbiased manner using eye‐tracking computer systems. Eleven of 30 screened patients and 9 next of kin completed study procedures. Patients reported good QoL, which appeared to be at the cost of the QoL of their next of kin. Next of kin rated their own or patients' QoL similarly, but they identified different areas as important as compared with patients. Our results are of importance for the discussion of end‐of‐life decisions and the evaluation of patients' presumed wishes as well as for psychosocial interventions. Ann Neurol 2017;81:310–315